(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article discusses the teachers’ teaching methodology and creative approach, the purpose of the pedagogical science, the types of modern creative methods used in the teaching of subjects and their use. In addition, the professional skills of teachers, their pedagogical features and their types were discussed.